Sequential kidney–liver transplantation from the same living donor for lecithin cholesterol acyl transferase deficiency. Issue 10 (24th September 2016) - Ahmad, Sarwat B.; Miller, Michael; Hanish, Steven; Bartlett, Stephen T.; Hutson, William; Barth, Rolf N.; LaMattina, John C.
Abstract: Background: Lecithin cholesterol acyl transferase (LCAT) deficiency is a rare autosomal recessive disorder of lipoprotein metabolism that results in end‐stage renal disease (ESRD) necessitating transplantation. As LCAT is produced in the liver, combined kidney and liver transplantation was proposed to cure the clinical syndrome of LCAT deficiency. Methods: A 29‐year‐old male with ESRD secondary to LCAT deficiency underwent a sequential kidney–liver transplantation from the same living donor (LD). One year following the kidney transplant, auxiliary partial orthotopic liver transplant (APOLT) of a left lateral segment from the same donor was performed. Results: At 5 years follow‐up, there have been no major complications, readmissions, or rejection episodes. Serum lipid abnormalities recurred within the first year, but liver and kidney allograft function remains intact. Conclusion: Few cases of sequential transplantation from the same LD have been performed in adults. This is the first APOLT and multi‐organ transplant performed for LCAT deficiency. Sequential organ transplant from the same LD for ESRD secondary to a metabolic disorder of the liver is feasible in adults and should be further investigated.